Electromyographic activity in the cross-reinnervated soleus muscle of unrestrained cats. - Luff, A R (1985)
Electromyographic (e.m.g.) activity was recorded from cross- and self-reinnervated soleus and extensor digitorum longus (e.d.l.) muscles of the cat during normal activity, including standing, walking and jumping. Activity patterns of normal soleus, e.d.l., and lateral gastrocnemius (l.g.) were essentially similar to those shown by other investigators. The self-reinnervated soleus fired phasically and synchronously with l.g. during walking but the activity was not trimmed to the extent that is seen in normal soleus. This is attributed to the relatively limited amount of proprioceptive information arising from such muscles. The activity pattern of the cross-reinnervated soleus muscles was variable. During walking, the phase of activity was sometimes coincident with that of a normal e.d.l., at other times (even in the same animal) it would be approximately coincident with l.g. The phase of activity usually consisted of an initial burst which was not sustained. Reflex activity elicited from the cross-reinnervated soleus was very similar to that of normal e.d.l., indicating the rigidity of connexions for reflex responses. reinnervated e.d.l. muscles; the activity attributable to the cross-reinnervated portion was similar to that seen in a self-reinnervated soleus. The activity pattern of soleus, reinnervated by the nerve to e.d.l. (an effective antagonist) is unlike that of either a normal soleus or e.d.l. muscle. This is attributed to a combination of lack of proprioceptive information and/or some degree of central remodelling.